IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) MENGENAI PELAKSANAAN RENCANA K3 DAN PENINGKATAN KINERJA SMK3 DI PT. PLN PERSERO - Layla Hanum Batubara; Susilawati (CV. ADIBA AISHA AMIRA, 2024)
K3 Management System is a K3 management process that is integrated into a complete management system starting from the stages of planning, implementation, measurement, and supervision. The International Labour Organization (ILO) considers the implementation of SMK3 in Indonesia unsatisfactory and states that Indonesia is ranked second lowest in the world in the application of K3. The purpose of this literature study is to analyze from previous research on the implementation of the K3 plan and the improvement of SMK3 performance at PT. PLN (Persero). Research method This research uses literature review study methods and is qualitative. Literature search using a database in the form of secondary data from scientific articles / journals with the web using Google Scholar, or official article websites. Results a). Implementation of the K3 Plan, some companies have implemented K3 planning well but there are still those who are not aware of the use of PPE recommended rules. b). Review and Performance Improvement SMK3 has implemented regular review carried out in the form of meetings for 1 year in order to maintain maximum performance improvement of SMK3 at PT. PLN (Persero). Conclusion The Occupational Health and Safety Management System (SMK3) at PT PLN (Persero) is well implemented and follows the Standard Operation Procedure (SOP). However, there are some shortcomings in its implementation due to lack of proper planning and execution. System improvements and improvements are needed to ensure the continuity of the K3 system